The Control Structure for DC Motor based on the Flatness Control - Thang Nguyen Trong (Institute of Advanced Engineering and Science, 2017)
This article presents the new control structure for a Direct Current Motor (DC Motor) using the flatness-control principle. Basic on the mathematical model of DC Motors, the author demonstrates the application ability of the fatness-control theory to control the DC Motor, and then calculates the parameters and proposes the structure of the flatness-controller. The proposed structure is built and ran on Matlab-Simulink software to verify the system efficiency. The simulation results show that the quality of the control system is very good, especially in case of the flatness controller combined with PID controller to eliminate static error when the parameters of the DC Motor have been not known accurately.